Antimicrobial Activity Studies of Mixed Ligand Metal Complexes of Some Dibasic Acid and Heterocyclic Bases - Hossain, Md Belayet; Hassan, Md Nazmul; Yousuf, MA; Salam, MA (Dhaka University Journal of Pharmaceutical Sciences, 2009)
Mixed ligand transition metal complexes of Cu(II), Co(III), Rh(III) and Pt(IV) ions with dibasic acids viz., diphenic acid and adipic acid as primary ligands and amine bases as secondary ligands have been synthesized. They were characterized by conventional physical and chemical analyses. The antibacterial and antifungal activities have been evaluated for the synthetic ligands. Disc diffusion methods were employed for antimicrobial assays against five pathogenic bacteria and two fungi. The complexes containing 8-hydroxy quinoline as secondary ligand were much more active than the other complexes. In addition, the complex [Rh(DA)(8-HQ)(H2O)2] (4) showed the highest antibacterial activity against all bacteria tested (where, DA = Diphenic acid, 8-HQ = 8-hydroxyquinoline) and the complex [Pt(A)2(Q)2] (3) showed the lowest. On the other hand, he highest inhibition of growth occurred by complex K[Cu(DA)(8-HQ)] (1) against the fungi Botryodiplodia theobromae and the lowest by complex [Rh(DA)(8-HQ)(H2 O)2] (4) against the fungi Colletotrichum gloesparioides. Key words: Biological activity, Diphenic acid, Heterocyclic amine, Mixed ligand complexes doi: 10.3329/dujps.v7i2.2170 Dhaka Univ. J. Pharm. Sci. 7(2): 145-148, 2008 (December)